Nesting Habitats of Lesser Adjutant Stork and their Environmental Challenges in Nagaon, Assam - Baishali Das; Shatabdi Biswas; Das, Jyotismita (Ecological Questions, 2025)
The Lesser Adjutant stork (Leptoptilos javanicus) is among the rarest stork categorized as Near Threatened according to the IUCN Red List of Threatened Species 2024, that is widely distributed throughout the Brahmaputra and Barak valleys of Assam. The present study evaluated nesting records and threat factors towards its survival and conservation in the Nagaon district of Assam. Five different nesting locations were studied and four different nesting trees were observed. The frequency of occurrence of nests in each tree species was calculated. Different threat factors were directly observed such as habitat destruction, human disturbance near nesting habitats, pollution in rivers and wetlands, application of harmful chemicals in agricultural practices, excess fishing practices in nearby wetlands, etc. This gradual increase in anthropogenic activities is affecting the stork population adversely. The current study will support future research by offering baseline data for analysis, enhancing conservation planning, and outlining the essential precautions for the Lesser Adjutant stork's protection.